Treatment of Sarcoidosis in US Rheumatology Practices: Data From the American College of Rheumatology's Rheumatology Informatics System for Effectiveness (RISE) Registry. Issue 3 (28th January 2022) - Hammam, Nevin; Evans, Michael; Morgan, Esi; Reimold, Andreas; Anastasiou, Christine; Kay, Julia L.; Yazdany, Jinoos; Schmajuk, Gabriela
Abstract : Objective: Sarcoidosis is often treated with glucocorticoids, although the use of biologics is growing. Prescribing patterns for biologics for patients with sarcoidosis in US rheumatology practices have never been examined. Given that there are no steroid‐sparing US Food and Drug Administration–approved therapies for sarcoidosis, we sought to characterize the real‐world treatment of sarcoidosis and to assess practice‐level variation in prescribing patterns. Methods: We conducted an observational study of patients with sarcoidosis using data from the Rheumatology Informatics System for Effectiveness (RISE) registry (2014–2018). The RISE registry represents an estimated 32% of the US clinical rheumatology workforce. Adult patients with ≥2 codes for sarcoidosis ≥30 days apart were included. We examined sarcoidosis‐specific medication use at any time during the study period. Data were analyzed at the practice level. Results: A total of 3, 276 patients with sarcoidosis from 184 practices were included. Of those patients, 75.1% were women, with a mean age of 59.0 ± 12.5 years; 48.3% were White and 27.6% were Black. Overall, 59.3% of patients were prescribed glucocorticoids, and 24.7% received prolonged glucocorticoid therapy (≥10 mg/day for ≥90 days). In all, 12.1% received a biologic or targeted synthetic disease‐modifying antirheumatic drug (tsDMARD), most commonly tumor necrosis factor inhibitors. There was wide practice‐level variation among 31 practices with ≥30 patients with sarcoidosis; biologic use ranged from 15.6% to 69.2%. Infliximab represented the most common biologic prescribed. Conclusion: In a large sample of US rheumatology practices, 12.1% of patients with sarcoidosis received biologics or tsDMARDs. We found high variability in biologic use across practices. The significant use of long‐term glucocorticoids suggests unmet therapeutic needs in this patient population.